2018
DOI: 10.1097/fch.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Health and Health Care From the Perspective of Intimate Partner Violence Adult Female Victims in Shelters

Abstract: Intimate partner violence (IPV) predicts poor health for victims and their children, but little is known about the perspective of victims. This study reports the perspectives of adult female IPV victims about the impact of IPV on their health and barriers of health care access for themselves and their children. The majority rated their health as good to excellent (69%). However, 83.5% indicated that IPV negatively affected their health; 53.5% had unmet health care needs. Mental health care was the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 88 publications
2
23
0
1
Order By: Relevance
“…The association between exposure to physical IPV during the past 5 years and perceived need for help for exposed women was more than threefold that of unexposed women. Our results are in line with previous research based on clinic and convenience samples, indicating that many women exposed to IPV perceive the need for help in terms of care [9, 15]. Our study showed that among women exposed to physical IPV who also perceived a need for help, the majority sought primary health care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The association between exposure to physical IPV during the past 5 years and perceived need for help for exposed women was more than threefold that of unexposed women. Our results are in line with previous research based on clinic and convenience samples, indicating that many women exposed to IPV perceive the need for help in terms of care [9, 15]. Our study showed that among women exposed to physical IPV who also perceived a need for help, the majority sought primary health care.…”
Section: Discussionsupporting
confidence: 92%
“…Perceived need for help is therefore a crucial step before seeking care [14]. Previous research from the United States, using data from shelters, found that twice as many women exposed to IPV reported the need for mental health care compared with those reporting the need for physical health care (40.4% and 19.2% respectively) [15]. To date, there has been a lack of population-based studies exploring the association between exposure to IPV, perceived need for help and primary health care utilization within a Swedish context.…”
Section: Introductionmentioning
confidence: 99%
“…These perceptions may have been the situation prior their empowerment for they showed no courage to end violence but ended up accepting the abusive situation. Hence, it is recommended that in the administration of services to IPV victims, health care providers should be profoundly sensitive and sympathetic, so that by understanding their worldview, victims can be inspired to participate in rehabilitative or empowerment programs (Çalıkoglu et al, 2018;Wadsworth, Kothari, Lubwama, Brown, & Frank Benton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…47 Such interventions are acceptable to recipients, especially when coordinated with other needed services. 48 …”
Section: Intimate Partner Violencementioning
confidence: 99%
“…47 Such interventions are acceptable to recipients, especially when coordinated with other needed services. 48 Expanding and ensuring access to legal advocacy may have health benefits outside of addressing intimate partner violence, including improved housing and income. 49 Timely and easy access to legal advocacy without out-of-pocket costs will be important for people seeking support.…”
Section: We Strongly Recommend Interventions That Include Legal Advocacy and Supportive Interventions For Victims Of Intimate Partner Viomentioning
confidence: 99%